Nitric Acid Pulping of Dendrocalamus strictus Nees - Dhawan, Rita (Indian Forester, 1980)
Dendrocalamus strictus was pulped by nitric acid process. Air-dry chips were cooked with nitric acid and sodium nitrite. The residual wood was extracted with dilute solution of caustic soda. The material was washed, disintegrated and screened. The yield of the pulps was determined. It was observed that by the addition of sodium nitrite upto a certain extent, delignification was enhanced. Pulps were analysed for Klason lignin content, pentosan content, nitrogen content, ash content and permonganate number. It was observed that the yield, Klason lignin content, pentosan content and permonganate number of pulps decrease with increase in concentration of nitric acid, cooking time and temperature.